2008
DOI: 10.4049/jimmunol.181.2.1043
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Contraction of the CD8+ T Cell Response toward Lymphocytic Choriomeningitis Virus Infection in Mice Lacking Serglycin

Abstract: We previously reported that the lack of serglycin proteoglycan affects secretory granule morphology and granzyme B (GrB) storage in in vitro generated CTLs. In this study, the role of serglycin during viral infection was studied by infecting wild-type (wt) mice and serglycin-deficient (SG−/−) mice with lymphocytic choriomeningitis virus (LCMV). Wt and SG−/− mice cleared 103 PFU of highly invasive LCMV with the same kinetics, and the CD8+ T lymphocytes from wt and SG−/− animals did not differ in GrB, perforin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 59 publications
2
26
0
1
Order By: Relevance
“…In agreement with this notion, the absence of serglycin causes impaired storage of granzyme B both in Con A-induced CTLs (18) and in CD8 + T lymphocytes and NK cells from mice infected with lymphocytic choriomeningitis virus (20).…”
Section: Serglycin Regulates Apoptosissupporting
confidence: 65%
See 1 more Smart Citation
“…In agreement with this notion, the absence of serglycin causes impaired storage of granzyme B both in Con A-induced CTLs (18) and in CD8 + T lymphocytes and NK cells from mice infected with lymphocytic choriomeningitis virus (20).…”
Section: Serglycin Regulates Apoptosissupporting
confidence: 65%
“…It was therefore somewhat surprising that serglycin 2/2 mice were able to clear lymphocytic choriomeningitis virus infection as efficiently as were WT animals (20). However, an intriguing finding was that the contraction of the CD8 + immune response was markedly delayed in serglycin 2/2 mice as compared with WT controls, and this could be attributed to sustained proliferation of the CD8 + cells (20). Hence, although not affecting the actual ability to clear virus infection, serglycin appears to control the magnitude and durability of the immune response.…”
Section: Impact Of Serglycin On Immune Regulationmentioning
confidence: 99%
“…It has recently been demonstrated that animals lacking SG spontaneously develop an enlargement of multiple lymphoid tissues/organs (11) and a markedly delayed contraction of the CD8 ϩ T cell response following virus infection (12). Although multiple explanations for these findings may apply, one possibility would be that the absence of SG affects the ability of certain leukocyte populations to undergo apoptosis.…”
Section: Serglycin (Sg)mentioning
confidence: 99%
“…Serglycin Null allele: viable; secretory granule defects in mast cells (Abrink et al 2004); dense core formation is defective in mast cell granules (Henningsson et al 2006); defective secretory granule maturation and granzyme B storage in cytotoxic T cells (Grujic et al 2005); no effect on macrophages (Zernichow et al 2006); platelets and megakaryocytes contain unusual scroll-like membranous inclusions (Woulfe et al 2008); enlargement of multiple lymphoid organs, decrease in the proportion of CD4 þ cells, more pronounced airway inflammatory response in older mice (Wernersson et al 2009); increased virulence of Klebsiella pneumoniae (Niemann et al 2007); defective regulation of antiviral CD8 þ T-cell responses (Grujic et al 2008). Agrn Agrin Null allele: embryonic lethal; reduced number, size, and density of postsynaptic acetylcholine receptor aggregates in muscles; abnormal intramuscular nerve branching and presynaptic differentiation (Gautam et al 1996(Gautam et al ,1999; smaller brains (Serpinskaya et al 1999); abnormal development of interneuronal synapses (Gingras et al 2007); increased resistance to excitotoxic injury (Hilgenberg et al 2002); reduced number of cortical presynaptic and postsynaptic specializations (Ksiazek et al 2007).…”
Section: Prg1mentioning
confidence: 99%